2023
DOI: 10.1101/2023.10.02.560421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza A virus NS1 effector domain is required for PA-X mediated host shutoff

Juliette Bougon,
Eileigh Kadijk,
Lucie Gallot-Lavallee
et al.

Abstract: Many viruses inhibit general host gene expression to limit innate immune responses and gain preferential access to the cellular translational apparatus for their own protein synthesis. This process is known as host shutoff. Influenza A viruses (IAVs) encode two host shutoff proteins: nonstructural protein 1 (NS1) and polymerase acidic X (PA-X). NS1 inhibits host nuclear pre-messenger RNA maturation and export, and PA-X is an endoribonuclease that preferentially cleaves host spliced nuclear and cytoplasmic mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Another open question is how NS1 promotes PA-X host shutoff activity. In addition to our results, a recent study by Bougon et al supports this idea, as they found some NS1 mutations abolished host shutoff in PR8-infected cells (36). Our results show that PA-X and NS1 do not simply have an additive effect on RNA downregulation, as PR8 NS1 has no effect on RNA levels on its own, as previously reported (47).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another open question is how NS1 promotes PA-X host shutoff activity. In addition to our results, a recent study by Bougon et al supports this idea, as they found some NS1 mutations abolished host shutoff in PR8-infected cells (36). Our results show that PA-X and NS1 do not simply have an additive effect on RNA downregulation, as PR8 NS1 has no effect on RNA levels on its own, as previously reported (47).…”
Section: Discussionsupporting
confidence: 91%
“…This discrepancy between ectopic expression and infection led us to discover that the viral protein NS1 promotes the host shutoff activity of PA-X. NS1 appears to promote RNA downregulation by PA-X mutants with low activity, suggesting that NS1 and PA-X proteins functionally interact in PA-X-driven host shutoff, as also recently suggested by Bougon et al 35 .…”
Section: Introductionmentioning
confidence: 65%